Dual antiplatelet therapy in patients requiring urgent coronary artery bypass grafting surgery: A position statement of the Canadian Cardiovascular Society - Fitchett, David (Pulsus Group Inc, 2009)
Acute coronary syndrome (ACS) guidelines recommend that most patients receive dual antiplatelet therapy with clopidogrel and acetylsalicylic acid (ASA) at the time of presentation to prevent recurrent ischemic events. Approximately 10% of ACS patients require coronary artery bypass grafting surgery (CABG) during the index admission. Most studies show that patients who receive ASA and clopidogrel within five days of CABG have an increase in operative bleeding. Current consensus guidelines recommend discontinuation of clopidogrel therapy at least five days before planned CABG to reduce bleeding-related events. However, high-risk individuals may require urgent surgery without delay, to reduce the risk of potentially fatal ischemic events. The present multidisciplinary position statement provides evidence-based recommendations for the optimal use of dual antiplatelet therapy to balance ischemic and bleeding risks in patients with recent ACS who may require urgent CABG. RECOMMENDATIONS: 1. All ACS patients should be considered for dual antiplatelet therapy with ASA and clopidogrel at the earliest opportunity, despite the possibility of a need for urgent CABG. 2. Those at high risk of an early fatal event (eg, with refractory ischemia despite optimal medical treatment, and with high-risk coronary anatomy (eg, severe left main stenosis with severe right coronary artery disease), should be considered for early surgery without discontinuation of clopidogrel. In patients with a high bleeding risk (eg, previous surgery, complex surgery) who are also at high risk for an ischemic event, consideration should be given to discontinuing clopidogrel for three to five days before surgery. Patients at a lower risk for ischemic events (most patients) should have clopidogrel discontinued five days before surgery. 3. For patients who have CABG within five days of receiving clopidogrel and ASA, the risk of major bleeding and transfusion can be minimized by applying multiple strategies before and during surgery. 4. Patients who receive clopidogrel pre-CABG for a recent ACS indication should have clopidogrel restarted after surgery to decrease the risk of recurrent ACS. 5. For patients with a recent coronary stent, the decision to continue clopidogrel until the time of surgery or to discontinue will depend on the risk and potential impact of stent thrombosis. Restarting clopidogrel after CABG will depend on whether the stented vessel was revascularized, the type of stent and the time from stent implantation. Clopidogrel should be restarted when hemostasis is assured to prevent recurrent acute ischemic events.